Self-reported knowledge and skills related to diagnosis and management of keratoconus among public sector optometrists in the Limpopo province, South Africa - Pheagane M. Nkoana; Vanessa R. Moodley; Khathutshelo P. Mashige (AOSIS, 2022)
Background: Keratoconus (KC) has been regarded as a rare condition, although recent studies, including those in South Africa, suggest it is common and is increasing in prevalence. Furthermore, South African-based studies have shown that KC is normally detected at advanced or severe stages. Knowledge and skills for examination, diagnosis and management of KC by optometrists are important for the early detection and management of the disease. Aim: This study aimed to evaluate self-reported knowledge and skills for examination, diagnosis and management of KC patients among public sector optometrists. Setting: Seven public hospitals of the Capricorn district of the Limpopo province, South Africa. Methods: A quantitative cross-sectional descriptive study design was used. A self-administered online questionnaire was used to collect data on demographic characteristics of participants and their knowledge, skills and practice for the diagnosis and management of KC. Results: Twenty-four optometrists (n = 24) with a mean age of 39 ± 5.67 years, 18 (75%) of whom were female, participated in the study. Nineteen (79%) reported that their hospitals did not have the appropriate equipment to examine, diagnose and manage KC patients. Lack of equipment, poor knowledge, skills and competencies, hospital's level of services, policy and lack of interest were cited as barriers to contact lens fittings in KC patients. Using a dichotomised summation of self-reported knowledge and skills of KC, 13 (54.2%) of the optometrists were knowledgeable and skilled on risk factors of KC and examining, diagnosing and managing KC patients. Conclusion: A significant proportion of optometrists did not have the appropriate knowledge and skills to examine, diagnose and manage KC patients. Lack of equipment and poor knowledge and skills were the main barriers to contact lens fittings in managing KC. Contribution: This article highlights the need for the district to upskill the optometrists through a structured programme with a theory and practical component and also provide the necessary equipment to enhance patient care.